2019
DOI: 10.3390/geosciences9050198
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Relationship between Precipitation and River Water in the Northern Carpathians Base on the Evaluation of Water Isotope Data

Abstract: The aim of this study is to investigate the stable isotope composition of precipitation and river water from the northeastern part of Romania. For this study, we collected monthly samples (for variable periods of time) of precipitation from six stations, and river water from three stations, between March 2012 and December 2017. The precipitation in the area is sourced mainly from the Atlantic Ocean, and secondarily from the Black Sea, local recycling being important especially in summer. We found that the seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…They are ideal indicators for studying water cycling and they have been widely used [14][15][16][17][18]. For example, Zanazzi et al [19] measured Utah Lake's water balance by using stable hydrogen and oxygen isotopes and found that the groundwater recharged by snow melting was the primary source of river water in the Utah Valley; Nagavciuc et al [20] tracked the relationship between precipitation and river water in the northern Carpathian Mountains based on water isotope data and found that temperature had a significant impact on the change of δD in the precipitation; Li et al [21] analyzed the hydrogen and oxygen isotopes of urban rivers and believed that the comprehensive influence of climate and human factors was an essential reason for the changes in isotopic characteristics of urban rivers; Qu et al [22] revealed the isotopic characteristics and water source of the Hemuqiao Basin in the small watershed of the lower Yangtze River by analyzing the Stable nuclide composition of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…They are ideal indicators for studying water cycling and they have been widely used [14][15][16][17][18]. For example, Zanazzi et al [19] measured Utah Lake's water balance by using stable hydrogen and oxygen isotopes and found that the groundwater recharged by snow melting was the primary source of river water in the Utah Valley; Nagavciuc et al [20] tracked the relationship between precipitation and river water in the northern Carpathian Mountains based on water isotope data and found that temperature had a significant impact on the change of δD in the precipitation; Li et al [21] analyzed the hydrogen and oxygen isotopes of urban rivers and believed that the comprehensive influence of climate and human factors was an essential reason for the changes in isotopic characteristics of urban rivers; Qu et al [22] revealed the isotopic characteristics and water source of the Hemuqiao Basin in the small watershed of the lower Yangtze River by analyzing the Stable nuclide composition of precipitation.…”
Section: Introductionmentioning
confidence: 99%